Natural convection of three-dimensional non-Newtonian nanofluids with Marangoni effects and inclined magnetic fields - Ahmed, Sameh E.; Elshehabey, Hillal M.; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2022)
Based on the various applications of the influence of the magnetic field in the convection flow especially in the inclined case, a very large number of published investigations can be found. Nevertheless, those studies were devoted to the case of two-dimensional included magnetic fields. For the three-dimensional (3D, for short) case, there are no attempts to examine these impacts. To this end, this investigation aims to present a formulation for the inclined magnetic field in case of the 3D non-Newtonian power-law nanofluids flow under the Marangoni effects. The basic aide is depending on introducing three inclination angles with X -, Y -,and Z-axis for the magnetic strength, namely, eta(x), eta(y) and eta(y), respectively. These angles satisfy the mathematical relation cos(2)eta(x) + cos(2)eta(y) + cos(2)eta(z) = 1. The flow domain is considered as 3D cubic enclosures with a top free surface that has linear distributions of the tension as a function in the concentration and temperature. The finite volume (FV) technique with 3D SIMPLE (Semi-Implicit Method for Pressure Linked Equations) technique is used to treat the mathematical formulations. The major findings disclosed that the inclination angles 0-90-90 and 45-90-45 give the higher double-diffusive comparing to the other values of the inclination angles. During variation of the inclination angles, the average Nusselt number; Nu(av) has a rate of changes up to 13.21% while the average Sherwood number; Sh(av) reaches 380.21%.
Keywords: Inclined magnetic strength; Double-diffusive; Power-law nanofluids; Marangoni effects; 3D flow